Comparison of Depression in Women with Primary and Secondary Infertility in Patients at OB/GYN OPD at Sharif Medical City, Lahore, Pakistan - Junaid Khan, Muhammad Sohaib Iftikhar, Ushna Noor, Reem Sulaiman, Tahira Qadeer, Muhammad Abdullah Iftikhar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the prevalence of depression in women with primary and secondary infertility presenting at Gynecology Outpatient Department at Sharif Medical City, Lahore, Pakistan. Methodology: This is a questionnaire based cross sectional study with a sample size of 138 male and female patients. This study was conducted in (OB/GYN OPD) in a tertiary care setting of Sharif Medical City, Lahore. Duration of the study was 1 month i.e. July 2021. Results: 74% of the patients suffered from infertility due to primary causes, while 26% had secondary infertility. Female infertility accounted for about 93% of infertility cases seen at the clinic while male factor infertility was only 7%. Symptoms of depression were more likely to be seen in women with primary infertility than those with secondary infertility. Conclusions: Despite infertility affecting both men and women, infertility in men is more likely to be under reported. In our study, women with primary infertility often experienced signs and symptoms of depression as compared to women with secondary infertility. In general, infertile women are more likely to be target of abuse, societal pressures, and expectations. Having a good support system can help alleviate most of these symptoms. More research needs to be done to establish a causal relationship between infertility and depression.